Including Students with Autism Spectrum Disorder in Regular Classrooms – Current Practices - Nabila Chauhdry (JIE, 2024)
There has been a tremendous increase in the prevalence of Autism Spectrum Disorder (ASD) in the last two decades. Present study was aimed at exploring current practices for including students with ASD in regular classrooms of Punjab and interpreting the findings in the context of international research. The study was qualitative in nature and data was collected by conducting interviews of professionals working with students having ASD in inclusive classrooms. Document analysis of recent international research articles for current practices was also done. Findings indicated similarities in perceived challenges by national professionals and international researches. But there were discrepancies in the selection and use of appropriate classroom strategies. International researches indicated that more inclusive practices such as cooperative learning strategies and use of UDL (universal design for learning) are effective for yielding positive results. On the other hand, professionals working in Punjab focused more on use of standardized interventions e.g. PECS (picture exchange communication system) and behavior management strategies. An important factor leading to this gap, as indicated in the findings of study, is a lack of appropriate training of teachers, both at pre-service and in-service level. Well-designed teacher trainings and promotion of evidence-based practices can positively contribute to developing more inclusion friendly strategies.